Dental caries and periodontal diseases in the ageing population: call to action to protect and enhance oral health and well‐being as an essential component of healthy ageing – Consensus report of group 4 of the joint EFP/ORCA workshop on the boundaries between caries and periodontal diseases. (March 2017) - Tonetti, Maurizio S.; Bottenberg, Peter; Conrads, Georg; Eickholz, Peter; Heasman, Peter; Huysmans, Marie‐Charlotte; López, Rodrigo; Madianos, Phoebus; Müller, Frauke; Needleman, Ian; Nyvad, Bente; Preshaw, Philip M.; et al.
Abstract: Background: Over the last two decades, progress in prevention and treatment of caries and periodontal diseases has been translated to better oral health and improved tooth retention in the adult population. The ageing population and the increasing expectations of good oral health‐related quality of life in older age pose formidable challenges to clinical care and healthcare systems. Aims: The objective of this workshop was to critically review scientific evidence and develop specific recommendations to: (i) prevent tooth loss and retain oral function through prevention and treatment of caries and periodontal diseases later in life and (ii) increase awareness of the health benefits of oral health as an essential component of healthy ageing. Methods: Discussions were initiated by three systematic reviews covering aspects of epidemiology of caries and periodontal diseases in elders, the impact of senescence on caries and periodontal diseases and the effectiveness of interventions. Recommendations were developed based on evidence from the systematic reviews and expert opinion. Results: Key messages included: (i) the ageing population, trends in risk factors and improved tooth retention point towards an expected increase in the total burden of disease posed by caries and periodontal diseases in the older population; (ii) specific surveillance is required to monitor changes in oral health in the older population; (iii) senescence impacts oral health including periodontitis and possibly caries susceptibility; (iv) evidence indicates that caries and periodontal diseases can be prevented and treated also in older adults; (v) oral health and functional tooth retention later in life provides benefits both in terms of oral and general quality of life and in terms of preventing physical decline and dependency by fostering a healthy diet; (vi) oral healthcare professionals and individuals should not base decisions impacting tooth retention on chronological age but on level of dependency, life expectancy, frailty, comfort and quality of life; and (vii) health policy should remove barriers to oral health care for vulnerable elders. Conclusions: Consensus was reached on specific actionable priorities for public health officials, oral healthcare professionals, educators and workforce planners, caregivers and relatives as well as for the public and ageing patients. Some priorities have major implications for policymakers as health systems need to adapt to the challenge by systemwide changes to enable (promote) tooth retention later in life and management of deteriorating oral health in increasingly dependent elders.